(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article analyzes the strategic task of creating a raw material base for the USSR textile industry and ending the Union’s dependence on foreign countries in the cotton sector by rapidly restoring and developing the cotton sector in Uzbekistan, and the implementation of appropriate measures, using materials from archival sources